Nutritional quality and in vitro gas production of Piptocoma discolor (Kunth) Pruski forage across contrasting landscapes in the Colombian Amazon Piedmont - Faver Álvarez; Paula Andrea Ríos-Parra; Fernando Casanoves; Armando Sterling; Isabel Cristina Molina-Botero (PLoS ONE, 2026)
This study aimed to evaluate the nutritional quality and in vitro total gas production of Piptocoma discolor (Kunth) Pruski forage collected from two contrasting landscapes (alluvial plain and hill) in the Colombian Amazon piedmont. To achieve this, leaf and non-lignified stem samples were collected from scattered trees in each landscape and analyzed for their nutritional composition, degradability, and gas production. Crude protein (CP) levels differed significantly between landscapes (p < 0.05), with higher concentrations in the alluvial plain compared to the hill (14.6% vs. 9.5%, respectively). A similar trend was observed for ash, phosphorus, and nitrogen content (p < 0.05). However, neutral detergent fiber (NDF) content was higher in the hill landscape. The concentrations of magnesium, potassium, calcium, sodium, zinc, manganese, copper, and iron did not differ significantly between landscapes (p < 0.05). Regardless of the landscape, P. discolor exhibited moderately acceptable degradability (72%). Cumulative gas production (CGP) at 96 h was significantly higher (p < 0.05) for forage collected in the hill landscape compared to the alluvial plain (66 vs. 53 ml CGP/g dry matter incubated, respectively). These results confirm the potential of P. discolor to improve ruminant nutrition and support sustainable silvopastoral practices in the region.